THE ROLE OF CONTENT AND LANGUAGE INTEGRATED LEARNING AT UKRAINIAN AND POLISH EDUCATIONAL SYSTEMS: CHALLENGES AND IMPLICATION - Mariya Leshchenko; Yuliana Lavrysh; Kateryna Halatsyn (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
At present, Ukrainian universities are immersed into current processes of internationalisation, academic mobility and engaging into a European context, that, consequently, give rise to numerous surveys on advanced pedagogical approaches to correspond the framework of general European language learning policy. The paper aims to describe and summarise the experience of Content and Language Integrated Learning implementation (CLIL) in Ukraine. With the view of objective assessment of the survey results, we considered comparing our experience, challenges and solutions with Polish universities experience since CLIL approach is widely used and made its own history with great outcomes in Poland. The qualitative data of our survey were gathered, evaluated and compared with those presented in published investigations of Polish experts. The key objectives are to identify operating CLIL models and strategies at Igor Sikorsky Kyiv Polytechnic Institute and to measure up functioning features of this approach by means of SWOT analysis. Moreover, the researchers disclose the approach advantages, drawbacks and recommendations for further discussion. In the paper, the authors also outline the peculiarities of ongoing coexistence and relation of English for Specific Purposes (ESP) and CLIL in tertiary education in terms of aims, tasks, resources, teachers' roles and outcomes. The research results show that ESP and CLIL are interrelated approaches, which both contribute to students' learning motivation as well as language and field-related content acquisition; CLIL is a key factor for universities to attract students and take high rates in educational ranking.